2011 IEEE Workshop on Applications of Computer Vision (WACV) 2011
DOI: 10.1109/wacv.2011.5711512
|View full text |Cite
|
Sign up to set email alerts
|

Information fusion in low-resolution iris videos using Principal Components Transform

Abstract: The focus of this work is on improving the recognition performance of low-resolution iris video frames acquired under varying illumination. To facilitate this, an imagelevel fusion scheme with modest computational requirements is proposed. The proposed algorithm uses the evidence of multiple image frames of the same iris to extract discriminatory information via the Principal Components Transform (PCT). Experimental results on a subset of the MBGC NIR iris database demonstrate the utility of this scheme to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Most of them implement data-level fusion for superresolution from multiple video frames, such as [20,21]. State-of-the-art in this context are principal components transform [2,18] combining multiple normalised iris textures at image-level obtained by different segmentation algorithms. As representative of the first group, Uhl et al [4] suggested different strategies to combine direct segmentation boundaries rather than texture feeding the combined model into the normalisation routine.…”
Section: Iris Segmentation Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them implement data-level fusion for superresolution from multiple video frames, such as [20,21]. State-of-the-art in this context are principal components transform [2,18] combining multiple normalised iris textures at image-level obtained by different segmentation algorithms. As representative of the first group, Uhl et al [4] suggested different strategies to combine direct segmentation boundaries rather than texture feeding the combined model into the normalisation routine.…”
Section: Iris Segmentation Fusionmentioning
confidence: 99%
“…Among these tasks, it is especially iris localisation and pupillary/limbic boundary detection which challenge existing implementations [2], at least for images captured under less ideal conditions. Examples of undesirable conditions are visible light imaging with weak pupillary boundaries, on-the-move near infrared acquisition with typical motion blur, out-of-focus images, or images with weak limbic contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Since Baker and Kanade first suggested SR algorithms specifically for faces [5], there has been a lot of research in face super-resolution (also called hallucination) [6]. Learning approaches have been also used with other biometrics including iris [7], [8], [9], [10]. However, one major limitation is that they try to develop a prototype iris using combination of complete images.…”
Section: Introductionmentioning
confidence: 99%
“…Note that they considered a protocol similar to MBGC, where they compare a video to a high quality still image. More recent works [7,8] explored the fusion in the feature domain using PCA or PCT but not on the same MBGC protocol as they usually degrade artificially the image resolution in their assessment stage.…”
Section: Introductionmentioning
confidence: 99%